지능형 아카이브 솔루션을 활용한 공개재분류 연구: 2020년 국가기록원 공개재분류 사업을 중심으로 - 송주형; Song, Zoo Hyung (Journal of Records Management & Archives Society of Korea, 2021)
Access re-review is a valuable and important task, but it is burdensome for archivists. Thus, an access re-review automation was proposed to address this. In this situation, the National Archives of Korea actually utilized the access re-review solution in the performance of the "2020 Access Re-Review Project" and compared and analyzed it with human work. The project was, however, not a research project centered on analysis on access re-review solutions, and it has a limited result in terms of experimental use of commercial programs. Nevertheless, in the current situation where there are only macro and superficial discussions on access re-review of intelligent archives, it would be meaningful to apply the access re-review solution to archivists in real businesses and examine the results. This paper seeks to discuss the practicality that can mitigate the task of access re-review through an analysis of use cases of access re-review solutions. 기록물 공개의 전(前)단계인 공개재분류 업무는 가치있고 중요한 업무다. 그러나 그 의미와 중요성과 별개로 일선 기록연구사에게는 귀찮고 부담스러운 업무이기도 하다. 이에 기록연구사의 업무 부담을 경감해주는 공개재분류 자동화가 제안되기도 했다. 이런 상황에서 국가기록원의 '2020년 공개재분류 결과 건별 입력 위탁사업' 수행 간 공개재분류 솔루션을 활용하였고, 이를 사람이 한 작업과 비교⋅분석해 보았다. 물론 해당 사업은 공개재분류 솔루션에 대한 분석과 연구가 중심인 연구용역 사업이 아니었고, 상용프로그램을 실험적으로 사용해 본 제한적 결과라는 한계는 존재한다. 그럼에도 지능형 아카이브의 공개재분류에 대한 거시적이고 피상적인 논의만 있는 현 상황에서 기록연구사가 활용가능한 공개재분류 솔루션을 실제 사업에서 활용한 결과를 살펴보는 것은 여러모로 의미가 있으리라 생각된다. 본 논문은 공개재분류 솔루션의 활용 사례에 대한 분석을 통해 공개재분류 업무를 경감시킬 수 있는 실질적이고 미시적인 차원의 논의이다.